2021
DOI: 10.1039/d0sc06138g
|View full text |Cite
|
Sign up to set email alerts
|

Tandem diaza-Cope rearrangement polymerization: turning intramolecular reaction into powerful polymerization to give enantiopure materials for Zn2+ sensors

Abstract: Herein, we report a new tandem diaza-Cope rearrangement polymerization synthesizing enantiopure polymers with defect-free C–C bond formation. Furthermore, these polymers can be applied as high-performance turn-on Zn2+ sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…34−39 The other six studies were experimental and utilized (orthoester-)Claisen rearrangements for peripheral modifica-tion of polyaramids and polyimides 41−44 or the surface of graphene oxide, 40 or diaza-Cope rearrangement to mediate step-growth polymerization of diamines and dialdehydes. 45 Lastly, formally sigmatropic 1,2-Brook rearrangements were recently utilized to do skeletal editing of polymer chains. 46,47 Though scarce, these precedents provide a sound framework for further advances.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34−39 The other six studies were experimental and utilized (orthoester-)Claisen rearrangements for peripheral modifica-tion of polyaramids and polyimides 41−44 or the surface of graphene oxide, 40 or diaza-Cope rearrangement to mediate step-growth polymerization of diamines and dialdehydes. 45 Lastly, formally sigmatropic 1,2-Brook rearrangements were recently utilized to do skeletal editing of polymer chains. 46,47 Though scarce, these precedents provide a sound framework for further advances.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More than a century since the first report of sigmatropic rearrangements in 1912, only 11 studies have explored them in the context of polymers. Five of these studies are theoretical: Roald Hoffmann and co-workers investigated intriguing hypothetical classes of polymers they called “sigmatropic shiftamers,” because they predicted sigmatropic shiftseither Cope rearrangements or [1, n ]-hydride shiftswould render the polymer fluxional along its entire backbone. The other six studies were experimental and utilized (orthoester-)­Claisen rearrangements for peripheral modification of polyaramids and polyimides or the surface of graphene oxide, or diaza-Cope rearrangement to mediate step-growth polymerization of diamines and dialdehydes . Lastly, formally sigmatropic 1,2-Brook rearrangements were recently utilized to do skeletal editing of polymer chains. , Though scarce, these precedents provide a sound framework for further advances.…”
Section: Introductionmentioning
confidence: 99%
“…176 More recent examples of diaza-Cope rearrangement/polymerization, reported by Choi and Hwang in 2021 and Doyle-Kirmse reaction/polymerization of bis(allyl sulfide)s and bis(α-diazoester)s reported by Wang in 2022, are ambiguous by our definition because the rearrangements take place as the polymer backbone is forming rather than after the fact. 177,178 Around the same time, our group provided an unambiguous example of polymer backbone editing via sigmatropic rearrangements. Namely, Ditzler and Zhukhovitskiy reported that Ireland-Claisen rearrangements (ICRs) can transform poly(ester)s into vinyl polymers.…”
Section: Rearrangements Of Polymer Backbonesmentioning
confidence: 94%
“…recently, monomer enchainment through a diaza-Cope rearrangement has been demonstrated (Scheme 3), 46 but the composition of the polymer backbone was static afterward. With these considerations and precedents in mind, we identified Brook 47 and Ireland-Claisen 48,49 rearrangements as powerful but unexplored retrosynthetic disconnections from poly(silyl ether)s to poly(acyl silane)s and from vinyl polymers to polyesters (Scheme 4A, B).…”
Section: Synpacts Synlettmentioning
confidence: 99%